2020
DOI: 10.2174/1568026620666200601161703
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Proof of Protein Misfolding and Interactions in Multifactorial Alzheimer's Disease

Abstract: Objective: Alzheimer's disease (AD) is a devastating neurodegenerative disorder, characterized by the extracellular accumulations of amyloid beta (Aβ) as senile plaques and intracellular aggregations of tau in the form of neurofibrillary tangles (NFTs) in specific brain regions. In this review, we focus on the interaction of Aβ and tau with cytosolic proteins and several cell organelles as well as associated neurotoxicity in AD. Summary: Misfolded proteins present in cells accompanied by correctly folded, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 135 publications
0
30
0
Order By: Relevance
“…Autophagy enhancers that can be utilized for the potential treatment of neurodegenerative diseases is receiving growing attention in recent studies [9,18,93,94]. It has been shown that the inactivation of mTOR by the lipophilic macrolide antibiotic rapamycin promotes the induction of autophagy [95].…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy enhancers that can be utilized for the potential treatment of neurodegenerative diseases is receiving growing attention in recent studies [9,18,93,94]. It has been shown that the inactivation of mTOR by the lipophilic macrolide antibiotic rapamycin promotes the induction of autophagy [95].…”
Section: Discussionmentioning
confidence: 99%
“…Considering that autophagy is involved in the degradation of abnormal protein aggregates and the clearance of misfolded proteins [6,[73][74][75], the stimulation of autophagic activity may serve as an effective approach in treating neurodegenerative disorders [18,76,77]. Therefore, based on the role of OGT inhibitors in facilitating autophagic activity in cortical neurons, we propose the modulation of O-GlcNAcylation levels by OGT inhibition as a potential therapeutic approach to prevent and treat neurodegenerative disorders associated with a deficit in the autophagy process.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, distinct biomarkers, which are essential to figure out the pathological characteristics of AD, have been observed in the cerebrospinal fluid (CSF) [9,10]. The advancement of AD is associated with three cardinal neuropathological features such as extracellular deposition of amyloid-β (Aβ) to produce neuritic plaques, intracellular neurofibrillary tangles (NFTs) and synaptic degeneration [11][12][13]. These pathological alterations arise in the neocortex, hippocampus, and other subcortical regions that are crucial for cognitive functions [14].…”
Section: Introductionmentioning
confidence: 99%